The Effect of Eco-efficiency on Firm Value with Financial Performance as a Moderating Variable - Arbi Arsi Ave Noor; Annisa Ilma Hartikasari; Iwan Fakhruddin; Rina Mudjiyanti (Mahameru Publisher, 2022)
Eco-efficiency is one of the ways companies can help realize the world agenda, namely the Sustainability Development Goals. This study aims to examine the impact of implementing eco-efficiency on firm value moderated by financial performance as measured by ROA and ROE. The sample taken consisted of panel data from 140 energy companies from 2017-2021. The data obtained was then analyzed using panel data regression. This study proves that eco-efficiency has a positive effect on firm value. Companies that implement eco-efficiency have a higher company value than companies that have not implemented the concept of eco-efficiency. financial performance ROA (return on assets) has a negative effect on firm value which indicates the performance of company management in using company assets is not managed effectively and efficiently. While the financial performance of ROE (return on equity) has no effect on firm value because there are companies that use profits for retained earnings and are not distributed to shareholders. Meanwhile, the results of testing financial performance variables using ROA (return on assets) and ROE (return on equity) proxies as moderators in this study cannot strengthen or weaken the relationship between eco-efficiency and firm value.